Efek Minyak Ikan Lemuru dan Minyak Kelapa Sawit dalam Ransum terhadap Kadar Kolesterol, Kadar Omega-3 dan Omega-6 dan Malondialdehyde (MDA) Daging Ayam Broiler: Effect of Lemuru Fish Oil and Palm Oil in Rations on Cholesterol Levels, Omega-3 and Omega-6 Content and Malondialdehyde (MDA) in Broiler Chicken Meat - Suci, Dwi Margi; Muhammad Daffa Andhika Putra; Rita Mutia (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
The study aimed to evaluate the use of fish oil (FO) and palm oil (PO) in broiler chicken rations on the cholesterol content, omega-3 and omega-6 content, and malondialdehyde (MDA) of broiler chicken breast meat. Two hundred broiler DOCs were used in this study. The DOC was randomized and placed into 20 cage units (4 treatments and 5 replications), then kept for 5 weeks. A completely randomized design was used in the study, with treatments being P0: 3% PO oil, P1: 2% PO and 1% FO, P2: 1% PO and 2% FO, and P3: 3% FO. The variables observed were cholesterol levels, omega-3 and omega-6 content, as well as malondialdehyde in broiler chicken breast meat, and the data were analysed for variance. The results showed that the use of different ratios of FO and PO in rations did not show any significant difference in cholesterol levels, increased omega-3 levels (p<0.05), but showed no effect on omega-6 levels. The treatments did not differ in MDA levels. It concludes that the use of 3% lemuru fish oil produces the highest omega-3 in broiler chicken breast meat compared to other treatments. Key words: cholesterol, lemuru fish oil, malondialdehyde, omega-3, palm oil